PERAN KEPERCAYAAN MEREK DALAM MEMEDIASI PENGARUH E-WOM TERHADAP KEPUTUSAN PEMBELIAN PRODUK CHATIME DI BALI - Padmawati, Ni Made; Suasana, I Gusti Agung Ketut Gede (E-Jurnal Manajemen, 2020)
Purchase decision is the result of a decision making process from the available choices or alternatives. Purchase decision is very important for the company.  Companies need to pay attention to factors that can improve purchase decision.  This study aims to determine the effect of e-WOM on purchase decision through brand trust in Chatime products in Bali.  This research was conducted in the Province of Bali.  The number of samples taken was 104 respondents.  The instrument used in this study was a questionnaire.  The analysis technique used is path analysis and sobel test.  Based on the results of the analysis, it was found that e-WOM had a positive and significant effect on brand trust e-WOM had a positive and significant effect on purchase decision, brand trust had a positive and significant effect on purchase decision, and this study also proved that brand trust was able to mediate the effect of e-WOM partially on purchase decision in Chatime products in Bali.  Keywords: purchase decision, e-WOM and brand trust